ANALISIS MANIK-MANIK DALAM PENELITIAN ARKEOLOGI - Nani Somba (Balai Arkeologi Provinsi Sulawesi Selatan, 2010)
Study of the beads in a particular geographic area can provide a description of the location of the ancient settlement, the spread of humans and the selection of land used for settlements. Similarly, taking into account qualitative similarities and differences between the beads from various sites, can be described as trade relations between the centers of settlement. In the study of archaeological experts to create analytical models that are used as a bridge to the past through the remains of their material, to determine various aspects of human life, among other things, the classification model, typological analysis, and mineralogical analysis. To reach an understanding in the context of space and time, so do contextual analysis and interpretation with seriation method and ethnographic analogy.Studi tentang manik-manik di wilayah geografis tertentu dapat memberikan deskripsi lokasi pemukiman kuno, penyebaran manusia dan pemilihan lahan yang digunakan untuk pemukiman. Demikian pula, dengan mempertimbangkan persamaan dan perbedaan kualitatif antara manik-manik dari berbagai situs, dapat digambarkan hubungan perdagangan antara pusat pemukiman. Dalam studi arkeologi, para ahli membuat model analitis yang digunakan sebagai jembatan ke masa lalu melalui sisa-sisa peninggalan yang ditemukan, untuk menentukan berbagai aspek kehidupan manusia antara lain, model klasifikasi, analisis tipologis, dan analisis mineralogi. Untuk mencapai pemahaman dalam konteks ruang dan waktu, maka dilakukan analisis dan interpretasi kontekstual dengan metode seriasi dan analogi etnografi.